Pengaruh Diklat Dan Pengalaman Kerja Terhadap Prestasi Kerja Serta Dampaknya Terhadap Pengembangan Karir Pegawai Di Balai Karantina Pertanian Kelas 1 Denpasar - Kristola, Dio; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen, 2014)
Job performance is one of the measurement of a person to gain career development. Without a satisfactory job performance it is difficult for the employee to develop his career. Education and training and work experience are some of the factors that affect the job performance. This research aims to know the influence of education and training and work experience on the job performance as well as their impact on employee career development. This research was carried out at the Balai Karantina Pertanian Kelas 1 Denpasar. The data was collected through interviews, observations and questionnaires. The hypotheseswas tested by using path analysis techniques, the results showed that education and training and work experience  partially has positive and significant influence on job performance. Education and training, work experience and job performance partially has positive and significant influence on career development. Keywords: education and training, work experience, job performance and career development